2008
DOI: 10.1177/039139880803101210
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic migration of a catheter fragment followed by disconnection of a totally implantable venous access port

Abstract: Totally implantable venous access ports (TIVAPs) are frequently used in oncology patients who require long-term courses of chemotherapy. We report a silent, but potentially hazardous complication of catheter fracture and hepatic migration in a 64-year-old male. The patient presented with a painful, rapid swelling of subcutaneous tissue around the port area during a saline flush. A chest radiograph showed that the disconnected catheter had separated from the port and was no longer in its original location. A ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…To our knowledge, only one case of fracture and embolization of a catheter in hepatic veins has been described in the literature. 2 Embolization is generally asymptomatic and is diagnosed when the port is punctured for infusion, to draw blood, or for heparinization and reflux of blood is absent, which should call attention to the possibility of embolization. In these cases, a simple chest X-ray can confirm diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one case of fracture and embolization of a catheter in hepatic veins has been described in the literature. 2 Embolization is generally asymptomatic and is diagnosed when the port is punctured for infusion, to draw blood, or for heparinization and reflux of blood is absent, which should call attention to the possibility of embolization. In these cases, a simple chest X-ray can confirm diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Three routes of entry to liver have been described: coming from the gastrointestinal tract (the most frequent), through the abdominal or thoracic wall, or via the bloodstream, which is very rare [6,7]. Usually, the foreign body, if acquired through the skin, is located in the liver convexity and is posterior if it migrated from the gastrointestinal tract.…”
Section: E18mentioning
confidence: 99%
“…Three routes are possible for such migration: percutaneous, gastrointestinal, or via the bloodstream [2][3][4]6,7]. Five pediatric cases, with a sewing needle in the liver, have been reported in the last 37 years, most of which required laparotomy (Table 1).…”
mentioning
confidence: 99%
“…They showed that CPFA increases the anti-inflammatory to pro-inflammatory mediators ratio, improves antigen presentation ability, and restores leukocyte responsiveness to a larger extent than HVHF. A silent, but potentially hazardous complication of catheter fracture in a totally implantable venous access port was reported by Wang et al (5). After a saline flush, the subcutaneous tissue around the port presented a painful, rapid swelling.…”
mentioning
confidence: 93%
“…Experimental techniques and theoretical models to evaluate the hydraulic resistance of vascular access have been proposed by Naka et al (18) and Andrew et al (19), respectively. Detection and care of the silent complications resulting from the fracture of a catheter, or the obstruction of the blood flow in the superior vena cava caused by the indwelling central venous catheter, have been reported and discussed by Wang et al (5) and Pipili et al (20). However, an important role in the failure of a vascular access is played by the formation of a biofilm in implanted cath-plications.…”
mentioning
confidence: 99%